ASR, Volume 17, n° 2, 2013 - Full Issue - Journal System (African Sociological Review, 2015)
Contents Editorial .............................................................1 General Issues Talking Heritage: Africa at the Crossroad of Tradition and Modernity Tom Sanya .......................................................2 Memory and Disenchantment in Nadine Gordimer’s None to Accompany Me and Zoe Wicomb’s Playing in the Light. Zuhmboshi Eric Nsuh .......................................24 The Phenomenon of Social Conversion Among Farmers in France: From Traditional Agriculture to the Spiriluna Superfood Philippe Stéfanini & Samuel Ravatua-Smith ..................................43 Research Papers Declining Job Security Level and Workers’ Performance in selected Banks, South Eastern Nigeria Aliyu Taofeek Kolawole, O.A. Ajani, A. L. Adisa .......................................55 Donner un sens au nom du festival de la ville: Les enjeux de la reconstruction des liens d’appartenance dans une ville tunisienne naissante Mouldi Lahma ......................................................71 The Management of Diabetes Among the Rural Poor in South Africa Olajide Oloyede .........................................................81 Land Use Correlates of Street Children in Ogbomosho, Nigeria Olufemi A. Fawole, David V. Ogunkan & Deborah S. Adekeye ..........................100